Willingness of People to Economic Behavior in the Conditions of e-Economy: e-Health Problems - T. N. Belyackaya; O. M. Maklakova (Цифровая трансформация)
A study was conducted of the readiness of the population of Belarus for economic behavior in the e-health market. It is believed that there is a low awareness of the possibilities of using services and goods provided by the population, as well as of the experience in obtaining data and services. Lack of alternative e-health, the possibility of learning to receive services, guaranteed security of data transmission.